A New Testament biblical theology : the unfolding of the Old Testament in the New - Beale, G. K. 1949- (Baker Academic, 2011)
G. K. Beale examines how the New Testament storyline relates to and develops the Old Testament storyline. Beale argues that every major concept of the New Testament is a development of a concept from the Old and is to be understood as a facet of the inauguration of the latter-day new creation and kingdom. --from publisher description